Anyone Can Code: The Art and Science of Logical Creativity - Arya, Ali (CRC Press, 2021)
“Ali Arya guides you in a fantastic journey full of creativity in a coherent way that allows the traveler to learn and build up over the knowledge acquired in previous chapters until the reader accomplishes skills to develop solutions using programming.” — Andrés A. Navarro Newball , Professor, Pontificia Universidad Javeriana Cali Colombia “An excellent book that teaches programming and software development the way it should be done: independent from a specific implementation language and focusing on the main principles that are fundamental and substantive to any kind of software production.” — Dr Marc Conrad , Principal Lecturer, University of Bedfordshire Anyone Can Code: The Art and Science of Logical Creativity introduces computer programming as a way of problem-solving through logical thinking. It uses the notion of Modularization as a central lens through which we can make sense of many software concepts. The book takes the reader through fundamental concepts in programming by illustrating them in three different and distinct languages, C/C++, Python, and Javascript. Key features: Focuses on problem-solving and algorithmic thinking instead of programming functions, syntax, and libraries. Includes engaging examples, including video games and visual effects Provides exercises and reflective questions. It gives the beginner and intermediate learners a strong understanding of what they are doing so that they can do it better and with any other tool or language that they may end up using later. About the Author: Ali Arya is an Associate Professor of Information Technology at Carleton University, Ottawa, Canada. He received his Ph.D. in Computer Engineering from the University of British Columbia in 2003. Ali has over 25 years of experience in professional and academic positions related to software development and information technology. He is passionate about computer programming that brings together logical and creative abilities.